Jobsheet Pemograman Sistem Embedded Jurusan Teknik Elektronika Industri di Sekolah Kejuruan - Luthfi Rauf Muthasim; Hansi Effendi; Herlin Setyawan (Jurnal Pendidikan Teknik Elektro, 2023)
Education is a process to build an individual character. Education is also an important tool in improving the quality of human resources in a positive direction. The learning process is one of the ways to realize National Development. It is the duty of actors to develop the complete Indonesian human being. The current period is a transitional period for Vocational Schools due to curriculum changes from the 2013 curriculum to an independent curriculum. In the independent learning curriculum in the Industrial Electronics Engineering major, quite a lot of changes have been made. The implementation of an independent curriculum will also have significant problems, because not all SMKs are ready to implement an independent curriculum, especially in the field of teaching materials used by teachers when teaching. This problem also occurs in one of the SMKs in the city of Padang, namely SMK Negeri 1 Sumatera Barat. Where the problem is that teachers still do not have a jobsheet for learning practicum microcontrollers that are contained in the Embedded Systems Programming subject. So the purpose of this research is to apply the microcontroller jobsheet in the Embedded Systems Programming subject. The research method used is the R&D research method. Then the results in this study obtained microcontroller jobsheets in the Embedded Systems Programming subject which had been declared valid by learning media experts and microcontroller learning experts. In addition, the jobsheet has also been declared practical by the Embedded Systems Programming subject teachers and students.